Takotsubo Cardiomyopathy Related Emotional Stress - Kristian S. Hartanto (HM Publisher, 2022)
Takotsubo cardiomyopathy (TTC) or Takotsubo syndrome is a syndrome indicated by the presence of temporary left ventricle (LV) regional systolic dysfunction which mimics the symptoms of myocardial infarction. TTS patients have been reported to experience severe and sudden emotional or physical distress and the previous diagnosis of psychiatric disorders may be reported among some of the patients indicating the relationship between an emotional stressor and cardiac dysfunction. The sympathetic nervous system and catecholamines play an essential role to mediate the effect of emotional stressors on the heart. This article briefly discusses the relationship between the emotional stressor and cardiac dysfunction in TTC.